Identifying the Lipidomic Effects of a Rare Loss-of-Function Deletion in ANGPTL3. (June 2021) - Blackburn, Nicholas B.; Meikle, Peter J.; Peralta, Juan M.; Kumar, Satish; Leandro, Ana C.; Bellinger, Melissa A.; Giles, Corey; Huynh, Kevin; Mahaney, Michael C.; Göring, Harald H.H.; VandeBerg, John L.; Williams-Blangero, Sarah; et al.
Abstract : Background: The identification and understanding of therapeutic targets for atherosclerotic cardiovascular disease is of fundamental importance given its global health and economic burden. Inhibition of ANGPTL3 (angiopoietin-like 3) has demonstrated a cardioprotective effect, showing promise for atherosclerotic cardiovascular disease treatment, and is currently the focus of ongoing clinical trials. Here, we assessed the genetic basis of variation in ANGPTL3 levels in the San Antonio Family Heart Study. Methods: We assayed ANGPTL3 protein levels in ≈1000 Mexican Americans from extended pedigrees. By drawing upon existing plasma lipidome profiles and genomic data we conducted analyses to understand the genetic basis to variation in ANGPTL3 protein levels, and accordingly the correlation with the plasma lipidome. Results: In a variance components framework, we identified that variation in ANGPTL3 was significantly heritable (h 2 =0.33, P =1.31×10 −16 ). To explore the genetic basis of this heritability, we conducted a genome-wide linkage scan and identified significant linkage (logarithm of odds =6.18) to a locus on chromosome 1 at 90 centimorgans, corresponding to the ANGPTL3 gene location. In the genomes of 23 individuals from a single pedigree, we identified a loss-of-function variant, rs398122988 (N121Kfs*2), in ANGPTL3, that was significantly associated with lower ANGPTL3 levels (β=−1.69 SD units, P =3.367×10 −13 ), and accounted for the linkage signal at this locus. Given the known role of ANGPTL3 as an inhibitor of endothelial and lipoprotein lipase, we explored the association of ANGPTL3 protein levels and rs398122988 with the plasma lipidome and related phenotypes, identifying novel associations with phosphatidylinositols. Conclusions: Variation in ANGPTL3 protein levels is heritable and under significant genetic control. Both ANGPTL3 levels and loss-of-function variants in ANGPTL3 have significant associations with the plasma lipidome. These findings further our understanding of ANGPTL3 as a therapeutic target for atherosclerotic cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.